The Role Of Salivary Glands In Phosphate Homeostasis - Tomo Mukai; Hiroko Segawa; Shohei Sasaki; Saori Ohnishi; Yasuko Ishikawa; Naoshi Horiba; Otoya Ueda; Kou-ichi Jishage; Naoshi Fukushima; Sawako Tatsumi; Shinsuke Kido; Ken-ichi Miyamoto (The Korean Society of Nephrology, 2012)
Hyperphosphatemia is recognized as a contributor to vascular calcification in patients with chronic kidney disease (CKD) and hemodialysis (HD) patients and is independently associated with cardiac mortality. Dietary inorganic phosphorus (Pi) restriction, and the Pi binders are important therapy for dialysis patients with hyperphosphatemia. Recent study reported that salivary secretion of Pi to be an important determinant of hyperphosphatemia in patients with CKD and in those with ESRD under chronic dialysis. In the present study, we investigated the role of type IIb sodium-dependent Pi transporter (Npt2b) on salivary Pi excretion in mice. The expression of Npt2b protein was detected at the apical side of duct cells in the salivary glands, suggesting that ductal cells appears to be able to reabsorb Pi, thereby modifying the Pi concentration in the final saliva. In wild-type mice (Wt mice) fed a high Pi diet, the levels of plasma and salivary Pi are significantly higher than those in mice fed a low Pi diet. In Npt2b+/- mice, the salivary Pi concentrations were significantly increased compared with those in Npt2b+/+ mice. Npt2b+/- mice with adenine-induced renal failure had low plasma and salivary Pi levels, and plasma creatinine and BUN levels compared with Npt2b+/+ mice treated with adenine. In conclusion, Npt2b is involved in Pi secretion by salivary glands.